Construction of a pharmaceutical care mode for cancer pain patients in primary care based on the Delphi method: an effective analysis - Xie, Han; Chen, Xinyi; Xue, Min; Li, Huaying; Ge, Yonghan; Ge, Weihong (Frontiers in Pharmacology, 2023)
Objective：Pain is one of the most common symptoms of cancer patients. Patients with advanced cancer are always transferred to primary medical institutions or treated with home medication due to their specific pathophysiological characteristics. Studies have shown that continuous pharmaceutical care can improve the effectiveness and safety of drug therapy for cancer pain patients in primary care, but no relevant research has been conducted in China. Based on the Delphi method, this study aims to construct a pharmaceutical care mode for cancer pain patients and analyze its effect in drug therapy treatment in the primary care in China.Methods：Pharmaceutical care mode for cancer pain patients in primary care was developed through two rounds of expert consensus. A total of 200 cancer pain patients from January 2022 to January 2023 in Nanjing Drum Tower Hospital were recruited and were divided into intervention group and control group. The self-developed pharmaceutical care mode in primary care was conducted in intervention group, while traditional pharmaceutical care mode was conducted in control group. Comparisons between groups were performed in terms of pain assessment rate, reasonable rate of pain assessment, pain score, and incidence of adverse reactions.Results： Initiative of experts in the two rounds of consultation were both 100%, with the authority coefficient of 0.83. The coordination coefficient of the second round was higher than that of the first round, indicating that the consistency of expert opinions was enhanced. There were 100 cases in each group, and 12 and 8 were lost to follow-up in intervention group and control group, separately.Compared with the control group, intervention group had significantly higher pain assessment rate, reasonable rate of pain assessment, while had significantly lower pain score and incidence of adverse reactions.